Talking Islamic Radicalism in Psychological Perspective - Saliyo Saliyo (UIN Sunan Kalijaga, 2017)
This article was written aims to explore why been up to lately rife with Islamic radicalism in the perspective of behavioral psychology. The events of shootings, suicide bombings, the destruction of economic resources has been a lot happened at the local and global level. Such events always identified with radical and terrorist behavior. More details such behavior was stigmatized by Islamic radicalism or Islamic terrorists. This article examines the problem of Islamic radicalism in the psychological perspective. There are some reasons why an individual or religious group do radical behavior. First there is the cultural acculturation and enculturation. Second there is the interpretation of verses of scripture with a radical interpretation by the actors and considered legitimate. Thirdly there is the role of the media who preach with unbalanced and give labeling. Fifth behavior is not political social economic equity in a particular religion and the state. Sixth is no imposition liberal capitalist ideology incompatible with religious ideology. Seventh existing emotional instability of the perpetrators, radicals or terrorists.